Academic librarians and libraries: four short essays and a funeral - Aguillo, Isidro F. (Anuario ThinkEPI, 2016)
The expected disappearance of the physical library at the academy is motivating librarians to assume new roles and develop new services, such as CRAI (resource center for learning and research), or information commons. CRAIs seek to overcome wishful thinking and lack of training with protocols and quality products such as CRIS, tools for the evaluation of the scientific production of the institution. Some authors criticize the lack of transparency of many CRIS products, which are private and not user friendly despite the technical quality, as well as the persistence of obsolete bibliometric techniques. In conclusion, the creation of a national super-CRIS is proposed, which should be managed by expert professionals and with political capacities.
Keywords: CRAI; Information commons; CRIS; Current research information systems; University library; Librarian profession; Management and evaluation of scientific production; Central measures.